Rancang Bangun Sistem Informasi Data Penduduk Berbasis Web (Studi Kasus: Kantor Desa Mekarsari Kecamatan Bojong Pandeglang-Banten) - Ahmad Nurul Fahmi; Joko Priambodo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Information systems are a combination of technology and human activities in activities to support management and operations. Population Data is individual data or structured aggregate data as a result of population registration and civil registration activities. The population data system currently running in Mekarsari Village, Bojong Pandeglang-Banten District is population data that still uses Microsoft Excel in its data collection so that there is a lack of security in population data and the data collection process takes a long time and the data is not well organized. From the analysis and design that has been done at the Mekarsari Village Office, Bojong District, it produces a web-based application that can overcome existing problems. The data collection technique in this study was carried out by means of observation and literature study and the method used was the waterfall model. This research resulted in a population data processing information system that can present information quickly and efficiently and can present the necessary reports.